1998
DOI: 10.1080/13668259800033731
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to attitudes of Israeli corporate executives toward the employability of persons with intellectual disability

Abstract: To cite this article: Arie Rimmerman (1998) Factors relating to attitudes of Israeli corporate executives toward the employability of persons with intellectual disability, Journal of Intellectual and Developmental Disability, 23:3, 245-254To link to this article: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…A few studies have examined the effect of organisation size on attitudes toward other disadvantaged groups, including job seekers with a disability. Although Levy and colleagues (1992) did not find a significant effect for organisation size on employer attitudes toward job seekers with a disability, employers in large organisations have elsewhere been reported to hold more favourable attitudes toward these individuals than do employers in small organisations (Levy et al, 1993;Rimmerman, 1998).…”
Section: Organisational Context Variables and Employer Attitudesmentioning
confidence: 95%
“…A few studies have examined the effect of organisation size on attitudes toward other disadvantaged groups, including job seekers with a disability. Although Levy and colleagues (1992) did not find a significant effect for organisation size on employer attitudes toward job seekers with a disability, employers in large organisations have elsewhere been reported to hold more favourable attitudes toward these individuals than do employers in small organisations (Levy et al, 1993;Rimmerman, 1998).…”
Section: Organisational Context Variables and Employer Attitudesmentioning
confidence: 95%
“…More updated studies have extended their spectrum of observer groups and examined, for example, teachers (Brook & Galili, 2001;Brook, Watemberg, & Geva, 2000;Lifshitz, Glaubman, & Issawi, 2004), school counselors (Erhard & Umansky, 2005), grandparents (Katz & Kessel, 2002), and corporate executives (Rimmerman, 1998). Other studies have focused on attitudes toward specific disabilities, such as developmental disabilities (Rimmerman, Hozmi, & Duvdevany, 2000), autism (Reiter & Vitani, 2007), and learning disabilities (Brook & Geva, 2001).…”
Section: Attitudes Toward People With Disabilities In Israelmentioning
confidence: 99%
“…There are some cultural differences regarding attitudes toward people with ID (Scior et al, 2010), including beliefs about the causes of ID (Lakhan & Sharma, 2010). However, much like studies from the United States and other Western cultures reviewed above, studies examining attitudes toward people with ID across borders and cultures have consistently found that attitudes toward people with ID are better when there is increased contact (Horner-Johnson et al, 2002;Morin, Rivard, et al, 2013;Ouellette-Kuntz et al, 2010;Rimmerman, 1998;Sermier Dessemontet et al, 2014;Siperstein et al, 2011;Yazbeck et al, 2004), supporting Allport' s (1954) intergroup contact theory, which predicts that increased direct contact with members of a marginalized group will generally improve attitudes toward members of that group.…”
Section: International Perspectivesmentioning
confidence: 74%